Description of Self Control with Student Compliance with School Rules at Public Junior High School 13 Semarang - Mutaqin, Andri Nur; Hendriyani, Rulita (Universitas Negeri Semarang, 2024)
School discipline compliance for students is an action that shows behavior in accordance with the norms or rules of discipline made and applied at school. School discipline compliance behavior by students can be influenced by various factors. The purpose of this study was to determine the description of the relationship between self-control and compliance behavior to obey school rules. The study used a correlational quantitative approach, focusing on the description of the relationship between Self Control in students wit school discipline compliance behavior, The study population was all ninth grade students of SMP Negeri 13 Semarang. The sample of students as respondents was 100 students. Data collection techniques using questionnaires, which after tabulated. The results of data analysis based on tabulation of student answer scores on question instruments that measure self control variables (X) and school discipline compliance variables (Y) show that: (1) The results of the classical assumption test of normality, show that the estimated results of the regression model equation of this study meet the requirements of the normality test. (2) The results of the product moment correlation test show a correlation coefficient value of 0.348. So it illustrates that there is a relationship between self-control and compliance with school rules in students. The output results of the coefficient value are positive, meaning that if self control increases, student compliance will also increase. The significance of the analysis results is 0.000<0.05, meaning that there is a significant relationship between self control and school discipline compliance.